#TITLE_ALTERNATIVE# - ANDRABI CAPRIZA, M
This project study about the effect of acquisition on company’s capital structure, it is especially on acquired company. The goal of this project is to know whether there is changing on capital structure between before and after acquisition. Capital structure is the mixture of debt and equity maintained by a firm that could be measure with long term debt ratio or debt-equity ratio [Ross, Westerfield, Jordan, 2003]. Another definition of capital structure is composition of permanent financing of the company, which is mixture long term financial of firms, where capital structure is financial structure minus current liabilities [A. Sawir, 2004]. Based on two fundamental theory which is different, so there are variables which are different, those variables are total liabilities to total equity ratio and long term liabilities to total equity ratio, that were taken from financial reports of public companies between before and after acquisition. The financial reports were taken by time series method, start from one year until five years before and after acquisition. The samples are 35 public companies that were taken randomly every year of acquisition, start from 1998 until 2005. Statistic method in testing hypothesis is t-test. The result, there is changing significantly on total liabilities to total equity ratio, this ratio will decrease if there is acquisition on the target firms. However, it doesn’t occur on long term liabilities to total equity ratio; in other words, there is no changing significantly by statistic test between before and after acquisition on this ratio. Other results, there are equity increasing significantly between before and after acquisition. It also occurs on acquired company’s long term liabilities, but the significant increase doesn’t occur on acquired company’s short term liabilities. These results is consistent with statistic test, which is showing long term liabilities to total equity ratio not change significantly based on statistic results.